2018
DOI: 10.1177/0046958018790164
|View full text |Cite
|
Sign up to set email alerts
|

The Affordable Care Act Attenuates Financial Strain According to Poverty Level

Abstract: We use data from the 2011-2016 National Health Interview Survey to examine how the Patient Protection and Affordable Care Act (ACA) has influenced disparities in health care–related financial strain, access to care, and utilization of services by categories of the Federal Poverty Level (FPL). We use multivariable regression analyses to determine the ACA’s effects on these outcome measures, as well as to determine how changes in these measures varied across different FPL levels. We find that the national implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…22,25 For example, federal, state, and county policy initiatives such as Medicaid eligibility expansions, health-care safety nets, and public health programs targeting rural communities may enhance financial well-being, insurance coverage, and access to health care at the county level. 17,[26][27][28][29][30] Although the national recommended surgeon-topopulation ratio by various authorities such as the Graduate Medical Education National Advisory Committee is approximately nine surgeons per 100,000 population, 31,32 surgeon-to-population ratios vary substantially across counties in the United States. 18,33 By one report, about 25% of the US population lives in a county without a general surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…22,25 For example, federal, state, and county policy initiatives such as Medicaid eligibility expansions, health-care safety nets, and public health programs targeting rural communities may enhance financial well-being, insurance coverage, and access to health care at the county level. 17,[26][27][28][29][30] Although the national recommended surgeon-topopulation ratio by various authorities such as the Graduate Medical Education National Advisory Committee is approximately nine surgeons per 100,000 population, 31,32 surgeon-to-population ratios vary substantially across counties in the United States. 18,33 By one report, about 25% of the US population lives in a county without a general surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…As states participating in BRFSS changed over this period and adoption of the Medicaid expansion varied by state, the impact of changes in the healthcare coverage system on health metrics among this low‐wage workforce could not be evaluated in these analyses. Some research has shown improved healthcare access and some health metrics following the implementation of the ACA, particularly in states that expanded Medicaid . However, the results of other studies highlight residual inequities in access to care due to structural issues ranging from the reluctance of some providers to accept Medicaid patients and inability to afford coinsurance, particularly among the working poor, to lack of transportation, childcare, and employer‐provided time off for preventive care visits .…”
Section: Discussionmentioning
confidence: 99%
“…In the years before the ACA, low-income women were less likely to receive lifesaving recommended cancer screenings [39]. A new study found that the ACA was associated with improvements in health care-related financial strain [40]. However, socioeconomic disparities remained in term of mammograms and Pap tests utilization.…”
Section: Discussionmentioning
confidence: 99%